Efektivitas Penerapan Model Kooperatif Tipe Think Pair Share Berbantu Alat Peraga terhadap Motivasi dan Hasil Belajar pada Materi Aljabar Kelas VII SMPN 1 Boyolangu - Rera Noerantika; Habibatul Latifah (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of this study is to determine the effectiveness of the use of the cooperative model of type think pair share assisted visual aids in terms of motivation and student learning outcomes on the subject of algebra. The research used is quasi-experiment (quasi-experiment). The data obtained were analyzed and tested with a parametric statistic of the F test and t-test. The results are as follows. 1) There is a difference in learning motivation between students who taught think pair share learning compared to students who taught conventional learning with sig value. 0.012 with an average of 4.74 and there are differences in learning outcomes with sig values. 0,000 with an average of 13.39. 2) There is an increase in student learning motivation due to the application of think pair share learning with sig value. 0,000 average increase of 13,55 and there is an improvement of student learning result with sig value. 0,000 average increase of 38.23.